A personalized approach to assessing and managing pain in patients with cancer - Dimitrijević Jelena (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
Cancer pain is the most frequent and most unpleasant symptom of malignant disease and can impact patient's quality of life and can significantly increase suffering, if left untreated. Up to date approach in cancer pain treatment include assessment of cause, mechanism, pain severity, pain modulators, assessment of total pain, formulation of individual treatment plan and monitoring of treatment safety and efficacy. Cancer pain can be caused by tumor, by antineoplastic treatment or can be related to comorbidities. Regarding its pathogenesis pain can be categorized as nociceptive, neuropathic or mixed. To measure pain severity numerical rating scale (0-10), visual analogue scale and verbal scale (mild, moderate and severe) are used. Cancer pain is a multidimensional and encompasses physical, psychological, social and spiritual dimension of pain and treatment of cancer pain requires a holistic and multidisciplinary approach (total pain concept) Whenever it is possible and medically valid the best approach in treatment of cancer pain is treatment of its cause. If treatment of cause is not possible pain is treated with pharmacotherapy and non-pharmacological methods. Adequate and optimal treatment of cancer pain improves quality of life and diminish suffering of patients and their families.